Terms of trade, catch-up, and home market effect: the example of Japan - Dieter M. Urban (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper explores theoretically and empirically the long run relation of the terms of trade (ratio of domestic and foreign prices of traded manufacturing goods) and economic growth of a pair of industrialized countries, one of which experiences a major catch-up process towards the other. It is shown theoretically that there is no mean reversion of the terms of trade towards PPP during a catch-up process, which suggests very long half-life times of terms of trade. Two theoretical interdependencies between the terms of trade and economic growth are offered: the home market effect and the productivity shock effect. These two effects are tested against each other in a cointegration analysis for Japan and the US from 1957 until 1997. Income appears to be a relevant variable to explain the terms of trade in the Post-Bretton-Woods era. The relevant empirical channel is the home market effect. However, financial market effects appear also to be relevant.
Keywords: F31; F41; O41; 330; convergence; real exchange rates; PPP; terms of trade; cointegration; Terms of Trade; Entwicklungskonvergenz; Kaufkraftparität; Kointegration; Schätzung; Japan; USA